Ensuring High Visibility of Passive Markers at Fixed Camera Gain Using Divide and Conquer Method - Retinger, Marek; Michalski, Jacek; Kozierski, Piotr; Drapikowski, Pawel (IEEE robotics and automation letters, 2024)
The letter presents a novel solution to determine exposure and threshold values for cameras in motion capture systems without excessive interaction with the user. The solution is based on the divide and conquer method, which ensures a fast and efficient search of the values. As the results have shown, users without specialist knowledge can significantly improve the tracking capabilities of the motion capture system, especially for smaller passive markers. The tests have proved that for spherical markers with a diameter of 7.9 mm, the full time tracking capabilities can be ensured based on the settings determined with the proposed method, what is difficult to achieve with the default settings. Moreover, the cameras utilisation can be increased, which should have a positive effect on the overall tracking quality. This makes it possible to use smaller and lighter-weight markers, which is desirable for small flying units with payload capacity of a few grams only. The primary tests were performed in the laboratory equipped with 12 OptiTrack Prime ^{x} 13W cameras. The dedicated programming interfaces (Motive API and Camera SDK) were used. The validation tests included a DJI Tello EDU unit with four markers attached. In addition to analysis and considerations, the document includes pseudocodes that clearly explain the idea behind the algorithms and allow for an easy implementation of the solution.